2013
DOI: 10.1002/cbf.2978
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of lipoic acid and mesna on cyclophosphamide‐induced haemorrhagic cystitis in mice

Abstract: The protective roles of lipoic acid (LA)/vitamin C (VC) and mesna on preventing cyclophosphamide (CYP)-induced haemorrhagic cystitis (HC) were investigated. Swiss mice were divided into five groups randomly. HC was induced by a single dose of CYP injection (150-mg kg(-1) bodyweight). Group I was injected with saline (four times in total) throughout as control group. Group II received CYP and three equal doses of saline. Group III received CYP and three doses of mesna, whereas Group IV (or Group V) received CYP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…administration of cyclophosphamide (Fig. 3), in agreement with independent evidence in mice (26). Systemic preadministration of polaprezinc at 400 mg/kg significantly prevented the cyclophosphamide-induced increase in the bladder malondialdehyde levels (Fig.…”
Section: Oral Preadministration Of Polaprezinc Inhibits Lipid Peroxidsupporting
confidence: 89%
“…administration of cyclophosphamide (Fig. 3), in agreement with independent evidence in mice (26). Systemic preadministration of polaprezinc at 400 mg/kg significantly prevented the cyclophosphamide-induced increase in the bladder malondialdehyde levels (Fig.…”
Section: Oral Preadministration Of Polaprezinc Inhibits Lipid Peroxidsupporting
confidence: 89%
“…Decreased activity of the enzymatic antioxidants such as SOD, CAT and GPx has been well demonstrated in CP toxicity [25,37,43]. Treatment with mesna and antioxidants (lipoic acid) restored the enzyme activities to some extent [32]. In the present study, SOD, CAT, and GPx activities significantly decreased in CP-administered rats when compared to the sham group.…”
Section: Discussionmentioning
confidence: 52%
“…a p < 0.05 with respect to control, b p < 0.01 with respect to control, c p < 0.001 with respect to control causes a significant increase in ROS level in bladder tissues. Administration of antioxidants ameliorates oxidative stress by reducing ROS levels in bladder tissues [32]. Several antioxidants, such as α-tocopherol [24], β-carotene [33], and melatonin [34,35] have similar effects on cystitis symptoms [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This micronutrient has low cost, is easily accessible and safe 10 . In addition, supplementation of vitamin C in combination with cytotoxic agents in experimental models with CLF has shown therapeutic potential 11,12,13 . Previous studies concluded that vitamin C supplementation is nephroprotective in mice exposed to cisplatin 14,15 , indicating that this nutrient can be beneficial when administered in combination with chemotherapy agents.…”
Section: Efecto Con La Suplementación De Vitamina C Sobre La Neutropementioning
confidence: 99%